BBB07 contributes to, but is not essential for, Borrelia burgdorferi infection in mice. Issue 10 (16th October 2020) - Hahn, Beth; Anderson, Phillip; Lu, Zouyan; Danner, Rebecca; Zhou, Zhipeng; Hyun, Noorie; Gao, Lihui; Lin, Tao; Norris, Steven J.; Coburn, Jenifer
Abstract : Borrelia burgdorferi, a causative agent of Lyme disease, encodes a protein BBB07 on the genomic plasmid cp26. BBB07 was identified as a candidate integrin ligand based on the presence of an RGD tripeptide motif, which is present in a number of mammalian ligands for β1 and β3 integrins . Previous work demonstrated that BBB07 in recombinant form binds to β1 integrins and induces inflammatory responses in synovial cells in culture. Several transposon mutants in bbb07 were attenuated in an in vivo screen of the transposon library in mice. We therefore tested individual transposon mutant clones in single-strain infections in mice and found that they were attenuated in terms of ID50 but did not have significantly reduced tissue burdens in mice. Based on data presented here we conclude that BBB07 is not essential for, but does contribute to, B. burgdorferi infectivity in mice.